Enhancing students' digital literacy: Evaluating the effectiveness of notion-based e-modules - Sumiati, Ika Dewi; Sari, Eka Puspita Kartika; Prasetya, Ferry Budi; Muslimah, Syayidah; Yixuan, Li (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to investigate the effect of using Notion-based e-modules to improve students' digital literacy. The study was implemented in the odd semester of the 2023/2024 academic. This study used a quasi-experimental method with a quantitative approach. The design of the study used a pretest-posttest control group design. The data obtained were analyzed using a t-test to compare the results. The finding of study shows that the average pretest and posttest scores in the control class show a difference score of (0.52) less than the experimental class (22.00). Meanwhile the percentage of score increase obtained in the control class is (0.79%) lower than in the experimental class (33.28%). So it can be concluded that the increasing score of students’ digital literacy in the experimental class higher than the control class. Based on the results of data analysis using the t-test showed a significant increase scores in posttest compared to pretest score (t(62)= 82.76, p<0,0001), the control group also showed increase scores but not significantly different between the pretest and posttest scores (t(59)= 1,95, p=0.0571). It can be interpreted that the experimental group showed a more significant increase compared to the control group. So, the conclusion of the study show that the use of Notion-based E-modules has a significant impact on improving students' digital literacy. Further research is recommended to expand the scope of subjects from other study programs and compare the effectiveness of Notion with other digital platforms.